Strategi Keberlanjutan Usaha Produk Sabun Padat Serai Melalui Pendekatan SWOT, HPP dan BMC bagi Usaha Rintisan - Roslina, Siti Nur; Septiani, Riana; Sundari, Susanti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The transformation of a start-up business for lemongrass soap products requires in-depth research for competitiveness and sustainability. This study aims to analyze the development of a start-up business producing lemongrass-based solid bath soap and its sustainability strategy in women's farmer group X. The approach used includes SWOT analysis, calculation of Cost of Goods Sold (COGS), and Business Model Canvas (BMC) to assess internal strengths, external opportunities, production cost efficiency, and the design of a sustainable business model. The results of the study show that the quantitative strategy analysis (IE/SWOT Matrix) places KWT X at coordinates (1.65; 1.15), which falls in Quadrant I (Aggressive). This position indicates that the company or business (KWT) has strong internal strengths (X Score: 1.65 > 0) and is in the midst of large external opportunities (Y Score: 1.15 > 0). So, KWT X's business is in a very favorable condition. The COGS calculation results show a production cost per unit of Rp9,000, with an ideal selling price of Rp12,500–Rp13,000 per unit to be competitive in the market. In addition, the implementation of the nine BMC elements confirms that KWT X has a strong business foundation through strategic partnerships, product diversification, and digital marketing. Product innovation, cost efficiency, and strengthening human resource capacity are key factors for the sustainability of the lemongrass-based herbal soap business.